Triple barcoding for a hyperparasite, its parasitic host, and the host itself: a study of Cyclocotyla bellones (Monogenea) on Ceratothoa parallela (Isopoda) on Boops boops (Teleostei). - Bouguerche, C.; Tazerouti, F.; Gey, D.; Justine, J.L. (Parasite, 2021)
Cyclocotyla bellones Otto, 1823 (Diclidophoridae) is a monogenean characterised by an exceptional way of life. It is a hyperparasite that attaches itself to the dorsal face of isopods, themselves parasites in the buccal cavity of ﬁshes. In this study, Cy. bellones was found on Ceratothoa parallela (Otto, 1828), a cymothoid isopod parasite of the sparid ﬁsh Boops boops off Algeria in the Mediterranean Sea. We provide, for the ﬁrst time, molecular barcoding information of a hyperparasitic monogenean, the parasitic crustacean host, and the ﬁsh host, with COI sequences.